Narrative strategies in the construction of Sandra Cisneros’ novel The house on Mango Street - Molina Espinoza, Ileana (2025)
Chicana writer Sandra Cisneros explores in her novel The house on Mango Street (1983) the construction of the patriarchal house as a physical and metaphorical prison for the female characters that inhabit this text. In this way, the writer examines the situation of many Chicana women in the United States who struggle, from their barrios, to build a place in a society that excludes them because of their ethnic origin and discriminates against them because of their condition as women. This provokes a double sense of marginality that imprisons them in the private space of the house. However, the protagonist Esperanza Cordero manages to free herself from this oppressive space and “build” her own house where she can take root and grow. This article analyzes the narrative strategies used by Cisneros in this text, which are closely related to the process of empowerment and liberation experienced by Esperanza in the search for building her own identity.